Antimeningococcal herd immunity in the Czech Republic--influence of an emerging clone, Neisseria meningitidis ET-15/37 - Kriz, P; Kriz, B; Svandova, E; Musilek, M (Epidemiology and infection, 1999)
For many years, invasive meningococcal disease in the Czech Republic occurred sporadically and was caused mainly by meningococci of serogroup B. In 1993, when a new clone (ET-15/37) emerged, the only phenotype found was C:2a:P1.2,5. In 1995, an antigenic variation of the ET-15/37 clone, B:2a:P1.2,5, occurred. The results of immunological surveys conducted in 1989 and 1996 were compared. A significantly higher proportion of 1996 sera than those collected in 1989 showed bactericidal antibodies against N. meningitidis B:2a:P1.2,5 (19.7 vs. 5.1%) and N. meningitidis C:2a:P1.2,5 (15.9 vs. 7.4%), consistent with increased herd immunity due to the spread of the new clone in the Czech Republic. There were differences in the age distribution of the positive sera.
Keywords: přirozená imunita; přenašečství; mladiství; lidé; Adult; Middle Aged; Neisseria meningitidis; Age Distribution; Meningococcal Infections; fenotyp; Infant; dítě; Prevalence; meningokokové infekce; věkové faktory; Immunity, Innate; Adolescent; Humans; Phenotype; Česká republika; předškolní dítě; lidé středního věku; Child, Preschool; séroepidemiologické studie; věkové rozložení; Czech Republic; prevalence; Age Factors; antigeny bakteriální; Carrier State; Child; dospělí; Seroepidemiologic Studies; Antigens, Bacterial; kojenec